2016
DOI: 10.1589/jpts.28.112
|View full text |Cite
|
Sign up to set email alerts
|

The perception of physical therapy leaders in Saudi Arabia regarding physical therapy scope of practice in primary health care

Abstract: [Purpose] To explore the views of the physical therapy service leaders in Saudi Arabia regarding the integration of physical therapy service in primary health care settings. [Subjects and Methods] A self-administered questionnaire consisting of both open and closed ended questions was distributed during May–July 2013 via email to physical therapy leaders representing different regions and health care providers in Saudi Arabia. [Results] Twenty-six participants answered the questionnaire. Eighty five percent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…These results are similar with that of a previous national survey exploring the perception of PT leaders in Saudi Arabia on the provision of PT service at PHC 26) . The results also reinforced that of previous studies, which showed that the establishment of PT within PHC resulted in high levels of satisfaction among patients and primary care physicians 12,19,31,32) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are similar with that of a previous national survey exploring the perception of PT leaders in Saudi Arabia on the provision of PT service at PHC 26) . The results also reinforced that of previous studies, which showed that the establishment of PT within PHC resulted in high levels of satisfaction among patients and primary care physicians 12,19,31,32) .…”
Section: Discussionsupporting
confidence: 90%
“…A cross-sectional survey using a self-administered questionnaire was developed by the authors based on clinical experience and relevant literature 26,27) . An expert panel of five physical therapists in different specialties, each with more than 10 years of professional experience, was formed to review the instrument.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Although a large number of patients received care in physiotherapy, its services have not been involved as primary health care. 20 Furthermore, although physiotherapists are permitted to make assessments for patients, design plans of care and apply treatments, 19 patients do not have the ability to access physiotherapy services directly in MOH hospitals, but they can refer themselves to private practice.…”
Section: Introductionmentioning
confidence: 99%
“…In SA, physiotherapists face some challenges including lack of evidence-based practice implementation among physiotherapists 12 ) and lack of postgraduate physiotherapy programmes in Saudi universities 13 ) . In addition, direct access to physiotherapists is not allowed in SA and all patients need physicians’ referral to receive a physiotherapy session 13 ) , as well as inability of physiotherapists to be involved in primary health care centres 14 ) . Furthermore, a recent study conducted by Al-Eisa et al found that 75% of physicians did not refer any patients or rarely referred patients to physiotherapy clinics in SA 15 ) .…”
Section: Introductionmentioning
confidence: 99%